Customer Relationship Management Implementation and its Implication to Customer Loyalty in Hospitality Industry - Hardjono, Budiono; San, Lai Pooi (JDM (Jurnal Dinamika Manajemen), 2017)
Building up customer loyalty have become more important to survive in the high competition of hospitality industry. One approach to developing this is by implementing customer relation-ship management (CRM). This study investigates the implication of CRM implementation to-wards customer loyalty in the hospitality industry. The results should assist marketers to recog-nize what determinant factors and dimension of CRM that contribute to building up customer loyalty in the hospitality industry. A purposive survey of 150 respondents of all rated hotels in Malacca, Malaysia was conducted. It is found that there is a significant correlation between customer orientation, CRM organization, and knowledge management towards customer loy-alty while the another dimension of technology-based CRM has no significant effect on this research. The marketer in the hospitality industry should, however, carefully evaluate the nature of customer loyalty regarding any other variables that are not included such as brand image and brand association and some special or unique features in this hospitality industry that should be addressed in the future research.